Positioning idealism with the power of Waspada newspaper review of the van Leeuwen theory - Pohan, Jusrin Efendi (Diksi, 2022)
This research is motivated by the problem of conspiracy between idealism and power in the context of critical discourse analysis studies. The domination of power makes idealism lose its resonance as a pillar of truth and justice which is marked by resistance and trust from its readers. This needs to be studied academically with The van Leeuwen's theory in the perspective of critical discourse analysis. The purpose of this study is to photograph the relationship between power and idealism, marginalization, and conspiracies of the mass media and their readers. In Theo van Leeuwen's theory, a problem is analyzed by exclusion and inclusion based on ideology. This type of research is a qualitative research that describes descriptively the problems in the Nusantara column in the North Sumatran Waspada newspaper. The source of the research data was obtained from the Nusantara column in the Waspada newspaper by analyzing the items per sentence according to Theo van Leeuwen's theory. Keywords: Idealism, Power, Critical Discourse Analysis